已知x,y=[1,2],[3,4]z=[x,y,x+y]则表达式z[1][1]+z[2][2]结果是
A: 4
B: 5
C: 6
D: 7
A: 4
B: 5
C: 6
D: 7
举一反三
- 已知a=[[1,2,3],[2,2],[3,2,1]],则a[1][1]+a[-1][-1]结果是 A: 1 B: 2 C: 3 D: 4
- 下列Python语句的输出结果是。 x=y=[1,2] x.append(3) print(x is y,x==y,end=') z=[1,2,3] print(x is z,x==z,y==z)
- 以下代码的显示结果是什么? data=[[[1,2],[3,4]],[[5,6],[7,8]]] print(data[1][0][0]) A: 1 B: 2 C: 4 D: 5 E: 6
- 计算 [(x, y) | x - [1, 2], y - [1, 2]] 的结果是 A: ([1,2],[1,2]) B: [(1,1),(1,2),(2,1),(2,2)] C: [(1,1),(2,1),(1,2),(2,2)] D: [(1,1),(2,2)]
- 以下程序的输出结果是: ls=[[1,2], 'python', [[3,4,'A'],5],[0,7]] print(ls[2][1]) A: 'A' B: p C: 3 D: 5